Odpowiedź :
Odpowiedź:
[tex]5( \sqrt[3]{4} ) {}^{3} = 20[/tex]
[tex]4 \sqrt[3]{5} \times \sqrt[3]{5} \times \sqrt[3]{5} = 4( \sqrt[3]{5} ) {}^{3} = 20[/tex]
[tex] ({ \sqrt[3]{6} } )^{2} \times 2 \sqrt[3]{6} = 2( \sqrt[3]{6} ) {}^{3} = 12[/tex]
[tex]2 \sqrt[3]{7} \times 5( \sqrt[3]{7} ) {}^{2} = 10( \sqrt[3]{5} ) {}^{3} = 50[/tex]
[tex] - 3 \sqrt[3]{2} \times 5 \sqrt[3]{2} \times \sqrt[3]{2} = - 15( \sqrt[3]{2} ) {}^{3} = - 30[/tex]
[tex] - 4( \sqrt[3]{5} ) {}^{2} \times ( - 2) \sqrt[3]{5} = 8( \sqrt[3]{5} ) {}^{3} = 40[/tex]